THE INTERRATER RELIABILITY OF NURSING OUTCOME CLASSIFICATION (NOC): “SELF-CARE: EATING” ON MENTALLY DISABLED CHILDREN IN YOGYAKARTA - Hartini, Sri; K, Novi Aprilia; Nurjannah, Intansari; Haryanti, Fitri; Kholisa, Itsna Lutfi; Hapsara, Sunartini (Belitung Raya Foundation, Indonesia, 2018)
Background: The common problems suffered by children with intellectual disability are difficulty to perform of daily activities or self-care including eating activity. NOC Self-care: eating is a measurement of client’s status regarding eating skill after provides nursing intervention. NOC was translated into Indonesian and its indicators were operationalized. The measurement of self-care: eating need to be evaluated, thus the reliability of this instrument was tested to determine whether the NOC is also reliable for use in Indonesia. Objective: The aim of this study was to investigate the interrater reliability of the NOC: Self-care: eating in the Indonesian Language in children with intellectual disability. Methods: Two raters assessed 124 children with intellectual disability using NOC: Self-care: eating. The study was conducted on December 2017 to January 2018. NOC was translated into Indonesian and each indicator was operated. Kappa and percent agreement were used for the analysis. Results: The overall kappa value of NOC: Self-care: eating was 0.55, while the percent agreement was 88. The highest kappa value and percent agreement was indicator of swallowing the food (0.8 and 99). Conclusions: The interrater reliability of NOC: Self-care: eating in Indonesian was at the level of great reliability.